2016
DOI: 10.3171/2015.4.spine141310
|View full text |Cite
|
Sign up to set email alerts
|

Use of neuropathic pain questionnaires in predicting persistent postoperative neuropathic pain following lumbar discectomy for radiculopathy

Abstract: OBJECT Failed-back surgery syndrome has been historically used to describe extremity neuropathic pain in lumbar disease despite structurally corrective spinal surgery. It is unclear whether specific preoperative pain characteristics can help determine which patients may be susceptible to such postoperative disabling symptoms. METHODS This prospective study analyzed surgical microdiscectomy patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…The findings reflect a high reported success rate for lumbar discectomy compared to RCT data [3] if based on leg pain as the measured outcome, with success clear for patients immediately following surgery. This is interesting and contrasts previous findings that the presence of features of neuropathic pain accompanied by higher scores of neuropathic pain was associated with persistent leg pain [35]. Mean disability prior to surgery was 53.33, illustrating a moderate level of disability.…”
Section: Statement Of Principal Findingscontrasting
confidence: 90%
“…The findings reflect a high reported success rate for lumbar discectomy compared to RCT data [3] if based on leg pain as the measured outcome, with success clear for patients immediately following surgery. This is interesting and contrasts previous findings that the presence of features of neuropathic pain accompanied by higher scores of neuropathic pain was associated with persistent leg pain [35]. Mean disability prior to surgery was 53.33, illustrating a moderate level of disability.…”
Section: Statement Of Principal Findingscontrasting
confidence: 90%
“…Furthermore, none of the included studies reported if participants had neuropathic pain characteristics, such as dysaesthesia (impaired sensation) and allodynia (pain resulting from a stimulus which would not normally provoke pain). Previous research has shown that higher scores of neuropathic pain and the presence of neuropathic pain features are associated with persistent postoperative leg pain (Shamji and Shcharinsky, ). It is unclear if included studies are screened for these characteristics, and could have potentially included participants more likely to develop failed back surgery syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the lumbar transforaminal endoscopic decompression procedure is by far less burdensome to the patient and realizes direct cost savings not just by virtue of being carried out in an ASC, but also due to its much lower individual complication rates in areas where disproportionate expenditures can easily be accumulated once inpatient management of complications is required. In other words, the most common complications and sequelae of lumbar transforaminal endoscopic decompression were distinctly different from those reported with inpatient microdiscectomy [6][7][8][9][10][11][12][13] and were managed in an outpatient office setting and, thus, never registered as additional claims since acute postoperative care measures were covered and included in the 90-day global payment period during the first 6 postoperative weeks.…”
Section: Discussionmentioning
confidence: 99%